I-DBSCAN Algorithm with PSO for Density Based Clustering - Neha; Verma, Prince (International Journal of Computer Sciences and Engineering, 2019)
The data mining is the approach which extracts useful information from the rough information. The clustering is the approach of data mining which cluster the similar and dissimilar type of information. The clustering techniques is of various type which hierarchal clustering, density based clustering and so on. The IDBSCAN algorithm is the density based clustering algorithm. The density based clustering has the various algorithms. In this research work, the I-DBSCAN algorithm is improved using the PSO algorithm to increase accuracy of clustering. The proposed methodology is implemented in MATAB and results are analyzed in terms of accuracy.